Trophy hunting : behavioral, demographic, and evolutionary consequences in ungulate populations : the example of the ungulates of African savannahs - (:unkn) unknown (My University, 2012)
Like predation, trophy hunting may constrain ungulates to adjust their behaviour todecrease mortality risk. Moreover, because this removal is size selective and male-biased, itmay induce morphological changes towards individuals with smaller traits, alter populationstructure and dynamics. Trophy hunting is one of the conservation modes of naturalhabitats, particularly in Africa. However, its conservation potential is still unclear becausethere are few studies outside National Parks. This thesis aimed to investigate the subtleeffects of trophy hunting on African ungulates, i.e. on their behaviour, horn length ofharvested males, proportion of adult males, group size, and population densities. I workedfrom behavioural observations, and from population data of long-term surveys. For severalspecies (mainly impala Aepyceros melampus, greater kudu Tragelaphus strepsiceros, andsable antelope Hippotragus niger), I compared behaviour, population structure, anddensities between Hwange National Park and adjacent hunting areas, Zimbabwe. In huntingareas, I analysed trends in horn length of harvested males over the past 30 years. This thesisshows that ungulates drank more often at night, and were more vigilant in hunting areasthan in the national park. However, the amplitude of these adjustments was constrained bythe need of surface water, and by natural predation risk. Trophy hunting caused a decline inhorn length, particularly for species that experienced high hunting pressure and were ofhigh value for hunters. Trophy hunting tended to decrease proportion of adult males,though not significantly, and did not affect group size. Moreover, during the last 30 years,ungulate densities generally declined more in the national park than in neighbouringhunting areas. This suggests that trophy hunting played a minor role on densities comparedto other factors, i.e. rainfall, and possibly natural predation and elephant densities. Despitebehavioural adjustments induced by hunti
Keywords: African Research